Adaptasi Patung Si Gale-Gale sebagai Inovasi Rias Fantasi - Zahra Salma Syahida; Adhi Kusumastuti (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
This study aims to test the feasibility of adapting the Si Gale-Gale Statue as a fantasy makeup innovation. This background is based on the importance of preserving local culture through the development of creative makeup works. The research method used is Research and Development (R&D) with the ADDIE development model. The feasibility test was conducted by providing validation sheets to three beauty expert validators: a beauty lecturer, an artistic makeup expert, and a facial makeup expert. The data analysis technique used is quantitative descriptive analysis. The makeup results were evaluated based on five indicators: makeup, body painting, creativity, theme suitability, and feasibility of the development results. Based on the assessment of these five indicators, the qualification was